High-dose chemotherapy with autologous haematopoietic stem cell support for relapsed or refractory primary CNS lymphoma: a prospective multicentre trial by the German Cooperative PCNSL study group - Kasenda, Benjamin; Egerer, Gerlinde (Leukemia, 2017)
To investigate safety and efficacy of high-dose chemotherapy followed by autologous stem cell transplantation (HCT-ASCT) in relapsed/refractory (r/r) primary central nervous system lymphoma (PCNSL), we conducted a single-arm multicentre study for immunocompetent patients (<66 years) with PCNSL failing high-dose methotrexate)-based chemotherapy. Induction consisted of two courses of rituximab (375 mg/m2), high-dose cytarabine (2 × 3 g/m2) and thiotepa (40 mg/m2) with collection of stem cells in between. Conditioning for HCT-ASCT consisted of rituximab 375 mg/m2, carmustine 400 mg/m2 and thiotepa (4 × 5 mg/kg). Patients commenced HCT-ASCT irrespective of response after induction. Patients not achieving complete remission (CR) after HCT-ASCT received whole-brain radiotherapy. Primary end point was CR after HCT-ASCT. We enrolled 39 patients; median age and Karnofsky performance score are 57 years and 90%, respectively. About 28 patients had relapsed and 8 refractory disease. About 22 patients responded to induction and 32 patients commenced HCT-ASCT. About 22 patients (56.4%) achieved CR after HCT-ASCT. Respective 2-year progression-free survival (PFS) and overall survival (OS) rates were 46.0% (median PFS 12.4 months) and 56.4%; median OS not reached. We recorded four treatment-related deaths. Thiotepa-based HCT-ASCT is an effective treatment option in eligible patients with r/r PCNSL. Comparative studies are needed to further scrutinise the role of HCT-ASCT in the salvage setting.